2021
DOI: 10.3390/antibiotics10091029
|View full text |Cite
|
Sign up to set email alerts
|

Optical DNA Mapping of Plasmids Reveals Clonal Spread of Carbapenem-Resistant Klebsiella pneumoniae in a Large Thai Hospital

Abstract: Carbapenem-resistant Klebsiella pneumoniae (CR-KP) in patients admitted to hospitals pose a great challenge to treatment. The genes causing resistance to carbapenems are mostly found in plasmids, mobile genetic elements that can spread easily to other bacterial strains, thus exacerbating the problem. Here, we studied 27 CR-KP isolates collected from different types of samples from 16 patients admitted to the medical ward at Siriraj Hospital in Bangkok, Thailand, using next generation sequencing (NGS) and optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…An important difference between PCR and ODM is that, while the PCR analysis reveals the presence of a specific gene, the ODM analysis determines on which plasmid a specific gene is located. This is important, for example, for epidemiological studies of bacterial transmission [19] and plasmid conjugation [24,26]; we have also shown, previously, that detecting identical plasmids in several samples can be a proxy for ongoing clonal outbreaks [25,27].…”
Section: Antibiotic Resistance Gene Identification In Clinical Fecal Isolatesmentioning
confidence: 55%
See 1 more Smart Citation
“…An important difference between PCR and ODM is that, while the PCR analysis reveals the presence of a specific gene, the ODM analysis determines on which plasmid a specific gene is located. This is important, for example, for epidemiological studies of bacterial transmission [19] and plasmid conjugation [24,26]; we have also shown, previously, that detecting identical plasmids in several samples can be a proxy for ongoing clonal outbreaks [25,27].…”
Section: Antibiotic Resistance Gene Identification In Clinical Fecal Isolatesmentioning
confidence: 55%
“…By combining the ODM technique with Cas9-mediated identification of resistance genes, the method can determine the number of different plasmids in a sample, their size, on which plasmid a certain resistance gene is located and also use the ODM barcode to identify and trace plasmids [20]. Our methodology has proven to be useful in understanding the role of plasmid conjugation, for example, in hospital outbreaks and recurring urinary tract infections [19,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found to harbor various antimicrobial resistance genes, such as extended-spectrum β-lactamase, carbapenemase, aminoglycosides resistance, fluoroquinolone resistance, and tet (A) gene. In Thailand, ST147 carrying bla NDM have been reported in several studies 24 , 77 . However, the major clonal group of K. pneumoniae- CG258, comprising ST11, ST258, and ST512, was not detected in our study 4 .…”
Section: Discussionmentioning
confidence: 96%
“… 35 , 36 We have used this method to identify plasmids from sequence databases and to trace plasmids during resistance outbreaks. 29 , 30 , 37 , 38 We have recently also presented a simplified version of the assay that detects resistance genes on plasmids using a microscope (Primo Star iLED) that is already present in laboratories in low- and middle-income countries for diagnosing tuberculosis. 39 …”
Section: Introductionmentioning
confidence: 99%